High‐Pressure High‐Temperature Single‐Crystal Diamond Type IIa Characterization for Particle Detectors. Issue 8 (26th February 2020) - Chernykh, Sergey V.; Chernykh, Alexey V.; Tarelkin, Sergey A.; Kondakov, Mikhail N.; Shcherbachev, Kirill D.; Trifonova, Ekaterina V.; Drozdova, Taisia E.; Troschiev, Sergey Yu.; Prikhodko, Dmitry D.; Glybin, Yury N.; Chubenko, Alexander P.; Britvich, Gennady I.; et al.
Abstract : Various samples of multisectoral high‐pressure high‐temperature (HPHT) single‐crystal diamond plate (IIa type) (4 × 4 × 0.53 mm) are tested for particle detection applications. The samples are investigated by X‐ray diffractometry, photoluminescence spectroscopy, Raman spectroscopy, Fourier‐transform infrared, and visible/ultraviolet (UV) absorption spectroscopy. High crystalline perfection and low impurity concentration (in the {100} growth sector) are observed. To investigate detector parameters, circular 1.0 and 1.5 mm diameter Pt Schottky barrier contacts are created on {111} and {100} growth sectors. On the backside, a Pt contact (3.5 × 3.5 mm) is produced. The {100} growth sector is proved to be a high‐quality detector: the full width at half maximum energy resolution is 0.94% for the 5.489 MeV 226 Ra α‐line at an operational bias of +500 V. Therefore, it is concluded that the HPHT material {100} growth sector is used for radiation detector production, whose quality is not worse than the chemical vapor deposition method or specially selected natural diamond detectors. Abstract : High‐pressure high‐temperature (HPHT) single‐crystal diamond {100} growth sector is used for radiation detector production, The photoluminescence spectroscopy method, X‐ray diffraction (XRD), Raman spectroscopy, Fourier‐transform infrared spectroscopy (FTIR), and visible/ultraviolet (UV) absorption are used for structural investigation. The quality of the grown material is not worse than that grown by the chemical vapor deposition method or specially selected natural diamond detectors.